MEDIAMORFOSIS ITU BERNAMA BOOKTUBE: ANALISIS RESEPSI TERHADAP PENONTON BOOKTUBE - Permatasari, Andalusia Neneng; Maulani, Izni Indrawati; Darmawan, Ferry; Nurrahmawati, Nurrahmawati (Master of Communication Science Program, Universitas Diponegoro, 2021)
This study aims to determine the audience's meaning regarding booktube. Booktube is content about books, such as book reviews, discussions with authors, video challenge, video bookshelf tour, book haul, etc on Youtube. This study uses a qualitative method with a reception analysis for participants belonging to the M Generations (Sesak Media Generation). Booktube interpreted differently by participants as audiences, which is interpreted as an ordinary content of YouTube that cannot replace conventional book reviews. Another interpretation of the audience regarding booktube is as a form that is not just ordinary content, but also a community and effort and attempt to increase the level of literacy in Indonesia.